Melatonin: A Potential Agent in Delaying Leaf Senescence. (2nd January 2021) - Zhao, Yu-Qing; Zhang, Zhong-Wei; Chen, Yang-Er; Ding, Chun-Bang; Yuan, Shu; Reiter, Russel J.; Yuan, Ming
Abstract: Delaying early leaf senescence is important for improving photosynthetic efficiency and crop productivity. Melatonin, a multitasking bio-stimulator, participates widely in plant development and stress responses. In recent years, the cumulative researches show that melatonin has the ability to delay senescence in plants. This review covers the most recent advances on the mechanisms of melatonin-mediated leaf senescence. Melatonin biosynthesis in senescing leaves employs an alternative pathway and is significantly regulated by light. Melatonin increases the thickness of leaf cuticle, wax accumulation and the ratio of palisade/spongy of senescing leaves to maintain intact leaf structure. Melatonin eliminates free radicals through a scavenging cascade reaction and induces antioxidants and antioxidant enzymes; and provides better protection against lipid peroxidation via arranging parallel to the bilayers at high concentration. Meanwhile, melatonin's ability to ensure high photosynthetic efficiency is predominantly attributed to the reduction of chlorophylls and chloroplast proteins degradation, and the acceleration of chlorophyll de novo synthesis. The dual role of melatonin-regulated autophagy is beneficial for maintaining cellular homeostasis. NACs, WRKYs and DREBs play essential roles in melatonin-controlled transcriptional reprogramming of senescing leaves. Additionally, melatonin improves the activity of cytokinin and auxin; and inhibits the action of abscisic acid, ethylene and jasmonic acid to impact indirectly leaf senescence. Epigenetic modification may be part of mechanisms of melatonin-mediated alterations in gene expression. Moreover, selection of germplasms rich in melatonin and application of genetic modification in agriculture are extensively discussed. Further studies are needed to detail the mechanisms of melatonin-mediated signaling transduction in leaf senescence.